Special Features of Lasing on N2, N2+, Ar, Ne, and CO2 Transitions Pumped by a Nanosecond Transverse Discharge; Russian Physics Journal; Vol. 59, iss. 6 - Ivanov N. G. Nikolay Georgievich (2016, 2016)
Title screen